Systematic Literature Review Potential of Sappan Wood Plants (Caesalpinia sappan L.) As Anticancer - Mutiah, Roihatul; Fathin, Fita Faniya (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Sappan wood (Caesalpinia sappan L.) is a plant known to have an effect as an anticancer. The use of sappan wood as an anticancer scientifically has done much research, but it has not been delivered holistically. Furthermore, a systematic literature review is needed to get a wider understanding and the data that is more accurate so that it can be a reference for the researcher in developing a new medicine for anticancer. This literature research has the purpose of determining the sappan wood‟s compound that has acted as an anticancer, determining the prediction of anticancer activity on sappan wood in silico method, and the activities of anticancer in vitro and in vivo studies, and also determining how the mechanism is to develop the compounds as an anticancer. This research uses a systematic literature review, and the data are obtained by the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-analyses). The article searching method uses a database in Google Scholar, ScienceDirect, SpringerLink, and PubMed, which is then analyzed so that the researcher obtains 27 suitable articles. The analysis result exhibits that the compound inside sappan wood that activity as an anticancer are brazilin, brazilein, sappanchalcone, 3-deoxysappanchalcone, caesalpiniaphenol G, dan caesalpiniaphenol H. Sappan wood is proven to have a prediction concerning anticancer activities in silico, and the anticancer activities in vitro and in vivo through several mechanisms. They are apoptosis induction, cell cycle inhibition, antimetastasis, antiproliferative, inhibition of HO-1 expression, and inhibition of BAF.